Integrasi Artificial Intelligence Dalam Strategi Pengambilan Keputusan Bisnis Digital Studi Pada Startup Teknologi Di Indonesia - Merlin (CV. SINAR HOWUHOWU, 2025)
The rapid advancement of digital technology has significantly transformed how companies, particularly technology startups, make business decisions. This study aims to analyze how Artificial Intelligence (AI) is integrated into digital business decision-making strategies among Indonesian startups. A qualitative descriptive approach was employed using a case study method involving several technology startups in Jakarta, Bandung, and Surabaya. Data were collected through in-depth interviews, participatory observations, and document analysis. The findings indicate that AI integration is most prevalent in data analytics, market forecasting, and customer service personalization. AI implementation has proven to enhance efficiency, accuracy, and speed in business decision-making processes. However, the study also identified key challenges such as limited human resources, high implementation costs, and ethical concerns regarding algorithmic transparency. The research highlights that successful AI adoption depends not only on technological readiness but also on organizational and cultural transformation toward data-driven decision making. These findings contribute to both theoretical understanding and practical applications for AI-based digital business strategies in Indonesia.